AKTTVITAS SELULASE, AMILASE DAN INVERTASE PADA TANAH KEBUN BIOLOGI WAMENA - M Rahmansyah; HJD Latupapua (BERITA BIOLOGI, 2003)
Enzymatic activities in soil as due to microbes action in organic matter degradation, lead to propose as indicators for determining soil degree enrichment.In this work, the enzymatic activities of cellulase, invertase and amylase were determined in tropical soil collected from Biological Research Station in Wamena. Result of measurement on five soil samples showed that cellulase activity occurred between 0.10 - 0.31 mg reducing sugar/g soil/hour in 2% Carboxymethylcellulose (CMC) substrate, and about 0.15 - 0.25 mg reducing sugar/g soil/hour in 0.5% Avicel substrate.Amylase and invertase assayed in 6% of amylum and 6% of sucrose substrates correspondingly; and its activities between 2.55 - 3.54 and 0.59 - 1.30 mg reducing sugar/g soil/hour, respectively. Correlation of enzymatic activities and soil organic-C content (1.35 - 2.70%) of soil layer was significant in selulase and amilase, but it was poor correlation in invertase activity.